Effect of L-Glycine on Carcass Parameters, Blood Biochemicals, and Jejunal Histomorphometry of Commercial Broiler Chicken - M.R., Shisodiya; V.D., Lonkar; A.S., Kadam; C.S., Mote; S.N., Jadhav; B.R., Kadam (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
A study was conducted for duration of six weeks on 240, day-old Cobb-430Y broiler strain chicks and randomly distributed to four groups each containing three replicates and 20 chicks per replicate. Group A was Negative Control (NC) contained 3% Low Protein (LP) diet containing 19.50, 18.00 and 16.50% crude protein (CP) for broiler pre-starter, starter and finisher phases, respectively. Positive Control (PC) group B contained standard protein 22.50, 21.00, and 19.50% CP as per breeder recommendation. No L-Glycine was added to NC and PC diets. Group C (NC+Gly1) was formulated by adding 0.640, 0.810, and 0.630% L-Glycine in NC diet to arrive 2.30, 2.30, and 2.00% digestible (Dig.) Gly + Ser levels while group D (NC+Gly2) was formulated by supplementation of 0.755, 0.985, and 0.740% L-Glycine in NC diet to arrive 2.40, 2.40, and 2.10% digestible Gly + Ser levels in broiler pre starter, starter and finisher diets respectively. Digestible Gly + Ser levels of NC group were 1.71, 1.56 and 1.43%; and of PC group were 2.02, 1.91 and 1.76%, respectively for broiler pre starter, starter and finisher diets. Ratio of dig. Met, Thr, Trp, Arg, and Val. ratioed to Lys. were balanced in all diets. All diets were isocaloric (3010, 3100, and 3200 kcal ME /kg) for broiler pre starter, starter and finishaer phases, respectively. Results showed that the L-Glycine supplementation in AA-balanced 3% LP diet did not affect per cent eviscerated yield, giblet yield, ready-to-cook yield, and breast meat yield but helped to reduce abdominal fat without altering serum biochemical parameters. Dig. Gly + Ser levels of 2.30, 2.30, and 2.00% (L-Glycine levels of 0.640, 0.810, and 0.630%) in 3% low protein (19.50, 18.00, and 16.50% CP) for broiler pre starter, starter and finisher diets helps to improve jejunal crypt depth leads to increasing cell renewal rate and maturation in the gut. Incorporation of L-Glycine is recommedded to maintain Dig. Gly + Ser levels of 2.30, 2.30, and 2.00% in broiler pre starter, starter and finisher phases with reduction of 3% CP in breeder recommended commercial broiler diet. Reducing dietary crude protein using L-Glysine without harming broiler performance could be economical.